Conflict and the Practice of the Christian Faith: The Anglican Experiment - Kaye, Bruce N. (The Lutterworth Press, 2011)
Front Cover -- Title Page -- Copyright information -- Dedication -- Contents -- Acknowledgments -- Introduction -- Part One: Conflict and Connection in the Church -- 1. Conflict and Connection in Early Christianity -- 2. Local Traditions and the Universal Church -- 3. Catholicity Without Leviathan -- 4. The Powers, Church, and Truth -- Part Two: Will the Current Anglican Experiment Go Anywhere? -- Introduction -- 5. Why the "Virginia Report" is Not Good Enough -- 6. The Windsor Report: The Questions Less Asked -- 7. Will the Windsor Process Lead to the Precipice? -- 8. Lambeth-A Conference Re-discovered? -- 9. Conflict, Catholicity, and Hope -- Bibliography -- Back Cover.